1998
DOI: 10.1159/000013789
|View full text |Cite
|
Sign up to set email alerts
|

Study of the Human Auditory Cortices Using a Whole-Head Magnetometer: Left vs. Right Hemisphere and Ipsilateral vs. Contralateral Stimulation

Abstract: Structural and functional asymmetries of the temporal lobe affect language development and may also play a role in a variety of disorders, ranging from specific language impairment to schizophrenia. Whole-head neuromagnetometers allow the noninvasive measurement of functional asymmetries since activity from both hemispheres is recorded simultaneously. In the present study, the location of the auditory cortices and their responsiveness to pure tones was compared between hemispheres in healthy human subjects. Da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

27
57
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(85 citation statements)
references
References 27 publications
27
57
1
Order By: Relevance
“…For example, right hemisphere N1m generators are of greater amplitude (Kanno et al, 1996) and cover a larger area (Zouridakis et al, 1998) in the auditory cortex than do left hemisphere N1m generators. In the present study, N1m source location was more anterior in the right than in the left hemisphere, which is in agreement with previous whole-head MEG studies (Mäkelä et al, 1993;Nakasato et al, 1995;Pantev et al, 1998). This observation can be explained by the fact that the left temporal plane of right-handed subjects is significantly more posterior than the right (Geschwind and Levitsky, 1968;Szikla et al, 1977).…”
Section: Differences Between Hemispheressupporting
confidence: 93%
“…For example, right hemisphere N1m generators are of greater amplitude (Kanno et al, 1996) and cover a larger area (Zouridakis et al, 1998) in the auditory cortex than do left hemisphere N1m generators. In the present study, N1m source location was more anterior in the right than in the left hemisphere, which is in agreement with previous whole-head MEG studies (Mäkelä et al, 1993;Nakasato et al, 1995;Pantev et al, 1998). This observation can be explained by the fact that the left temporal plane of right-handed subjects is significantly more posterior than the right (Geschwind and Levitsky, 1968;Szikla et al, 1977).…”
Section: Differences Between Hemispheressupporting
confidence: 93%
“…Previous MEG and EEG studies have revealed that activation in the auditory cortices of both hemispheres is stronger for contralateral auditory stimulation [11,[32][33][34][35]37,51,52]. These findings are further corroborated by results obtained in animal models [14,18].…”
Section: Introductionsupporting
confidence: 69%
“…There is fairly good agreement that both hemispheres respond more vigorously to contralaterally presented auditory stimuli as shown by studies using monaural [34,35,37,51,52] and spatial stimulation using 3D audio [11,32,33]. However, for stimuli presented laterally via ITD, some studies have reported contralaterally larger responses [28], while others have found no significant differences between contra-and ipsilateral stimulation [51].…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…Others undertaken more recently (typically utilizing fMRI) have demonstrated that the cortex is arranged into two mirror-symmetric gradients extending in an anterior-posterior orientation (Humphries et al, 2010). Our previous studies using MEG and those of other groups report the former finding that, at least for M100, the responses are arranged from high to low tones, medially to laterally or posteriorly to anteriorly along Heschl's gyrus (Pantev et al, 1988;Pantev et al, 1998;Huotilainen, 1995;Arlinger et al, 1982;Rosburg et al, 2000). Importantly, the methodological differences between these studies on tonotopy may explain the variability between studies.…”
Section: Discussionmentioning
confidence: 93%